Mitochondrial ferritin in the regulation of brain iron homeostasis and neurodegenerative diseases - Gao, Guofen; Chang, Yan-Zhong (Frontiers in Pharmacology, 2014)
Mitochondrial ferritin (FtMt) is a novel iron-storage protein in mitochondria. Evidences have shown that FtMt is structurally and functionally similar to the cytosolic H-chain ferritin. It protects mitochondria from iron-induced oxidative damage presumably through sequestration of potentially harmful excess free iron. It also participates in the regulation of iron distribution between cytosol and mitochondrial contents. Unlike the ubiquitously expressed H-ferritin, FtMt is mainly expressed in testis and brain, which suggests its tissue-related roles. FtMt is involved in pathogenesis of neurodegenerative diseases, as its increased expression has been observed in Alzheimer’s disease, restless legs syndrome and Friedreich’s ataxia. Studies from our laboratory showed that in Alzheimer’s disease, FtMt overexpression attenuated the β-amyloid induced neurotoxicity, which on the other hand increased significantly when FtMt expression was knocked down. It is also found that, by maintaining mitochondrial iron homeostasis, FtMt could prevent 6-hydroxydopamine induced dopaminergic cell damage in Parkinson’s disease. These recent findings on FtMt regarding its functions in regulation of brain iron homeostasis and its protective role in pathogenesis of neurodegenerative diseases are summarized and reviewed.